2010
DOI: 10.1007/s10565-010-9163-5
|View full text |Cite
|
Sign up to set email alerts
|

Snail regulates cell survival and inhibits cellular senescence in human metastatic prostate cancer cell lines

Abstract: CitationSnail regulates cell survival and inhibits cellular senescence in human metastatic prostate cancer cell lines. 2010, 26 (6):553-67 Cell Biol. Toxicol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(34 citation statements)
references
References 60 publications
2
32
0
Order By: Relevance
“…Moreover, the migratory potential of these cells was decreased by Snail siRNA treatment [25]. Clinically, Snail overexpression correlates significantly with lymph node [26] metastasis, histologic grade, and TNM stage [27]; however, factors resulting in the development of CSC-like properties have not been fully identified.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the migratory potential of these cells was decreased by Snail siRNA treatment [25]. Clinically, Snail overexpression correlates significantly with lymph node [26] metastasis, histologic grade, and TNM stage [27]; however, factors resulting in the development of CSC-like properties have not been fully identified.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that snail, a transcription factor and E-cadherin repressor, is a novel prognostic factor in many carcinomas (26-29). However, expression of snail in HC showed no significant relation to the expression of E-cadherin (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Forced expression of SNAIL in epithelial PC lines ARCaP E and LNCaP is sufficient to induce at least a partial EMT, as evidenced by altered biomarker expression and migration. In contrast, SNAIL inhibition in mesenchymal PC-3 cells induces epithelial biomarker expression [40]. Consequently, expression of SNAIL is thought to be both necessary and sufficient to induce EMT, but the relationship of SNAIL to human PC remains to be established.…”
Section: Preclinical Evidence Of Ep In Pcmentioning
confidence: 99%